PERANCANGAN MONITORING SUHU DAN KELEMBABAN GEDUNG BERBASIS SMART SENSOR - Nur Alam (Faktor Exacta, 2017)
Temperature is a parameter that becomes a convenience factor for building users. In addition to temperature, a factor that is very influential on the building maintenance process is moisture. Smart sensors designed and manufactured in this study have been successfully tested. Smart sensors made this has many advantages that is small size, easy to be placed in the corner of the room, as well as smart sensor is controlled and data monitoring results can be read via LabView, android and web. Software used in this research is Arduino IDE and also LabView. The results of this study have obtained data measurement and monitoring of temperature and humidity in real time through LabView software from building that is Building C PNJ. Temperature and humidity monitoring is done in real time at three times, ie morning, noon and afternoon. The results of temperature monitoring and humidity in the building can be monitored in real time and the data can be stored through notepad or excel format. The results of this temperature and humidity monitoring have also been calibrated with a benchmark. Calibration results occur a difference of 0.5 to 1 point, this becomes a measure in increasing the sensitivity of the smart sensor.